Effect of Extraction Methods on Antioxidant Activity of Papery Skin Extracts and Fractions of Maja Cipanas Onion (Allium cepa L. var. ascalonicum) - Nyi M. Saptarini; Yulia Wardati (The Scientific World Journal)
Extraction can be carried out at ambient temperature or high temperature to accelerate the extraction process of secondary metabolites from simplicia. This study aimed to determine the effectiveness of extraction methods on antioxidant activity of secondary metabolites of papery skin extracts and fractions of Maja Cipanas onion (Allium cepa L. var. ascalonicum). Extraction methods were maceration, percolation, reflux, and Soxhlet method, and then, concentrated extracts were fractionated by liquid-liquid extraction based on the polarity of secondary metabolites. Antioxidant activity was determined by the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The phytochemical screening showed that onion papery skin contained alkaloids, polyphenols, flavonoids, and tannins. The IC50 value of the extract, ethyl acetate fraction, and water fraction of the four extraction methods in the concentration range 25–400  μg/mL were in the range of 55.62–107.08, 31.31–84.06, and 126.05–139.82  μg/mL, respectively, while the IAA value was in the ranges of 0.25–0.49, 0.32–0.86, and 0.19–0.21, respectively. Variation in IC50 and IAA values indicate that the extraction method affects antioxidant activity, due to extracted secondary metabolites from simplicia. The highest antioxidant activity was an ethyl acetate fraction by the reflux method, while the lowest was water fraction by the percolation method.